Retraction: Food and social background of nasopharyngeal cancer patients in Jakarta (Faculty of Medicine Universitas Indonesia, 1998)
The Editorial Board wishes to apologize for publishing the following article in the Medical Journal of Indonesia, vol. 6 # 4, October-December 1997 edition.